UJI DAYA KECAMBAH LEGUM DESMANTHUS DENGAN SKARIFIKASI AIR PANAS PADA LAMA PERENDAMAN BERBEDA - Aholiab Aoetpah; Jacobus OEmatan; Agustinus Semang (Politeknik Pertanian Negeri Kupang, 2019)
Native pasture of semi-arid region in West Timor, Indonesia was low for the legume proportion was less than 10% as compared to that of the grass. Introducing shrub legume like Desmanthus could enhance the pasture quality. The hardseedness, however, was the barrier for germination. The time span of soaking the seeds in boiling water was one of the simple methods of scarification. A study has been conducted to measure the germination of Desmanthus leptophyllus and virgatus soaked in 80oC hot water at different soaking times. A completely randomised design with seven treatments and three replicates was utilised. The treatments were soaking the seeds for 0 (T0), 15 (T15), 30 (T30), 45 (T45), 60 (T60), 75 (T75) or 90 (T90) seconds before planting. Variables measured were germination rate, imbibed viable seeds, hard seeds, abnormal seeds and dead seeds. Data were analysed with one-way analysis of variance (ANOVA) SPSS 2014; SPSS Statistics for Windows, Version 23.0, IBM Corp, Armonk, NY, USA. The differences due to treatments were tested with Duncan’s test at P < 0.05 level. The results showed that soaking the seeds in hot water for 60 to 90 seconds enhanced germination up to 39 and 58% for Desmanthus leptophyllus (P < 0.05). Soaking the seeds of Desmanthus virgatus seeds for 30 to 90 seconds enhanced the germination rate ranging in between 50 and 66% (P < 0.05). It can be concluded that soaking the Desmanthus seeds in 80oC hot water was one of the simple scarification methods that can enhance the germination rate but the soaking time requires attention.Key words: Desmanthus, hot water, scarification